PENGEMBANGAN BAHAN AJAR DIGITAL PENDIDIKAN PANCASILA BERBASIS PROFIL PELAJAR PANCASILA KELAS V SDN 2 TUBANAN JEPARA - Arni Kristya Mardiana; Filia Prima Artharina; Khusnul Fajriyah (STKIP Subang, 2023)
The background of this research is the lack of teaching materials for Pancasila Education. The form of learning media still uses visual forms or pictures in textbooks. Most of the material in the Pancasila Education subject is almost dominant using rote learning, discussion and assignment methods, including the value material found in Pancasila. This study aims to develop digital teaching materials in learning Pancasila Education based on the Pancasila Student Profile. Digital teaching materials are adapted to the six main characteristics of the Pancasila student profile, including: Faith, piety to God Almighty and noble character; global diversity; worked together; independent; critical reasoning; and creativity, the six main characteristics are interrelated with one another so as to form characters who practice Pancasila values ​​in their daily life. This type of research uses research and development (R&D) methods, namely research used to produce certain products, and test product effectiveness. The subjects in this study were fifth grade students at SDN 2 Tubanan Jepara. The data in this study are indicators of the feasibility of digital teaching materials, using data collection methods in the form of interviews, documentation, questionnaires, and observations, as well as quantitative analysis of the results of media expert questionnaires, material expert questionnaires, class teacher response questionnaires, and student response questionnaires. Based on the results of the development of digital teaching materials for Pancasila Education based on Pancasila Student Profiles, it can be concluded that digital teaching materials have appropriate and practical criteria for use in learning Pancasila Education.